Chest x-ray in the COVID-19 pandemic: Radiologists' real-world reader performance. Issue 132 (November 2020) - Cozzi, Andrea; Schiaffino, Simone; Arpaia, Francesco; Della Pepa, Gianmarco; Tritella, Stefania; Bertolotti, Pietro; Menicagli, Laura; Monaco, Cristian Giuseppe; Carbonaro, Luca Alessandro; Spairani, Riccardo; Babaei Paskeh, Bijan; Sardanelli, Francesco
Highlights: Chest x-ray had a 89 % sensitivity detecting COVID-19 pneumonia during pandemic peak. Experienced radiologists had higher specificity than less-experienced ones. Overall and per-group sensitivity in detecting COVID-19 pneumonia increased over time. Overall and per-group accuracy in detecting COVID-19 pneumonia increased over time. Abstract: Purpose: To report real-world diagnostic performance of chest x-ray (CXR) readings during the COVID-19 pandemic. Methods: In this retrospective observational study we enrolled all patients presenting to the emergency department of a Milan-based university hospital from February 24th to April 8th 2020 who underwent nasopharyngeal swab for reverse transcriptase-polymerase chain reaction (RT-PCR) and anteroposterior bedside CXR within 12 h. A composite reference standard combining RT-PCR results with phone-call-based anamnesis was obtained. Radiologists were grouped by CXR reading experience (Group-1, >10 years; Group-2, <10 years), diagnostic performance indexes were calculated for each radiologist and for the two groups. Results: Group-1 read 435 CXRs (77.0 % disease prevalence): sensitivity was 89.0 %, specificity 66.0 %, accuracy 83.7 %. Group-2 read 100 CXRs (73.0 % prevalence): sensitivity was 89.0 %, specificity 40.7 %, accuracy 76.0 %. During the first half of the outbreak (195 CXRs, 66.7 % disease prevalence), overall sensitivity was 80.8 %, specificity 67.7 %, accuracy 76.4 %, Group-1 sensitivity being similar to Group-2 (80.6 % versus 81.5 %, respectively) but higher specificity (74.0 % versus 46.7 %) and accuracy (78.4 % versus 69.0 %). During the second half (340 CXRs, 81.8 % prevalence), overall sensitivity increased to 92.8 %, specificity dropped to 53.2 %, accuracy increased to 85.6 %, this pattern mirrored in both groups, with decreased specificity (Group-1, 58.0 %; Group-2, 33.3 %) but increased sensitivity (92.7 % and 93.5 %) and accuracy (86.5 % and 81.0 %, respectively). Conclusions: Real-world CXR diagnostic performance during the COVID-19 pandemic showed overall high sensitivity with higher specificity for more experienced radiologists. The increase in accuracy over time strengthens CXR role as a first line examination in suspected COVID-19 patients.